1993
DOI: 10.1136/bmj.306.6888.1299
|View full text |Cite
|
Sign up to set email alerts
|

Assessing long term backache after childbirth.

Abstract: and suggests that antenatal testing could prevent a significant proportion ofvertical infection.In a recent survey of all obstetric units in the British Isles, 51% were offering HIV tests only to women perceived as being at risk, 3% to all women, and the remainder had no formal policy.3 Our results show that in south east England, only 17% of live births to infected women are recognised before delivery. There is therefore considerable scope for improvement in antenatal HIV testing programmes.We thank the obste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
2
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(30 citation statements)
references
References 10 publications
1
26
2
1
Order By: Relevance
“…Our findings were consistent with the consensus that back pain symptoms during pregnancy are largely benign and are not associated with adverse pregnancy outcomes (4,14). The causative role of epidural in postpartum back pain is still controversial, but most short‐term follow‐up studies up to several months after delivery and the use of epidural do not support an increase in the incidence of new or persistent back pain symptoms in these patients (8–11). Our data of patients followed up to 24 months after epidural also did not show any positive association between epidural analgesia and persistent back pain symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings were consistent with the consensus that back pain symptoms during pregnancy are largely benign and are not associated with adverse pregnancy outcomes (4,14). The causative role of epidural in postpartum back pain is still controversial, but most short‐term follow‐up studies up to several months after delivery and the use of epidural do not support an increase in the incidence of new or persistent back pain symptoms in these patients (8–11). Our data of patients followed up to 24 months after epidural also did not show any positive association between epidural analgesia and persistent back pain symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of back pain in postpartum patients has also been quoted to be between 30% and 45% (8). This incidence is believed to be particularly high in those receiving epidural anesthesia during labor (9,10), despite the fact that the role of epidural in postpartum back pain is still controversial (8–11). However, the relationship of postpartum pain to antepartum back pain was only specifically evaluated in a few more recent studies (4,8) The reported incidence of persistent back pain symptoms also varied widely in the literature, from the disappearance of pain in more than 60% within 2 days after delivery (12) to approximately 37% at 12 months (13), to up to 82% at 18 months for those with recurrent back pain from previous pregnancies (14).…”
mentioning
confidence: 99%
“…7 This publication stimulated the conduct of several prospective observational studies and, later, randomised trials. These studies consistently demonstrated an absence of association between the use of epidural analgesia and back pain either in the first months post-partum [8][9][10][11][12] or longer term. [13][14][15][16][17] Unfortunately, this information has not been widely Headache and neck pain are also common post-partum symptoms, experienced by 40% of women in the first week after delivery.…”
Section: Introductionmentioning
confidence: 90%
“…[49] Russell ve ark. [50] retrospektrif yaptığı bir çalışmada da buna benzer rakamlar (%18) bildirilmiştir. Ancak bu iki ça-lışma, sadece doğum yapan kadınları değerlendiren bir çalışma olduğundan, sırt ağrısı sadece uygulanan epidural analjeziye bağlı değil, aynı zamanda travay sırasındaki pozisyona da bağlı olabilir.…”
Section: Discussionunclassified